PERSEPSI AKUNTAN INTERNAL TERHADAP PSAK 101-108 TENTANG AKUNTANSI SYARIAH PADA LEMBAGA KEUANGAN SYARIAH DI MALANG - Zubaidah, Siti (Faculty of Economics and Business, University of Muhammadiyah Malang, 2012)
The purpose of this study is to examine the perception of internal accountants to PSAK 101-110 of accounting sharia in Islamic financial institutions. This study used questionnaires given to internal accountant at Islamic Financial Institutions in the Malang. Technical analysis is descriptive qualitative, where the data collected by questionnaires. The results showed that the perception of internal accountants to SFAS 101-110 on the recognition, measurement, presentation and disclosure of transactions in the financial statements on average had agreed, either on murabaha accounting, accounting musharaka, mudaraba accounting, leasing, ijarah and presentation in the financial statements